2010
DOI: 10.1115/1.4002699
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Interaction Among Bullet, Body Armor, and Human and Surrogate Targets

Abstract: This study used a combined experimental and modeling approach to characterize and quantify the interaction among bullet, body armor, and human surrogate targets during the 10-1000 μs range that is crucial to evaluating the protective effectiveness of body armor against blunt injuries. Ballistic tests incorporating high-speed flash X-ray measurements were performed to acquire the deformations of bullets and body armor samples placed against ballistic clay and gelatin targets with images taken between 10 μs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It is broadly accepted that the short duration first peak is related to the initial impact event onto the body armour; the second and later peak is related to the macroscopic deformation of the armour into the body 17 31 32. Both peaks, but particularly the first, are affected by armour construction 25 32 37…”
Section: Resultsmentioning
confidence: 99%
“…It is broadly accepted that the short duration first peak is related to the initial impact event onto the body armour; the second and later peak is related to the macroscopic deformation of the armour into the body 17 31 32. Both peaks, but particularly the first, are affected by armour construction 25 32 37…”
Section: Resultsmentioning
confidence: 99%
“…compared able-bodied subjects to individuals with chronic spinal cord injury to investigate changes in soft tissue stiffness 10 . Finally, this dataset may be used to design clothing, protective equipment 11 , or sockets for artificial limbs 12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Based on the elastic modulus and tangent modulus, plastic hardening modulus E h can be calculated, as shown in equation (4).…”
Section: P=klnvmentioning
confidence: 99%
“…The results demonstrated that the differences between overpressure values of two models is within 10% under the same impact condition. Shen [4] used a combined experimental and modeling method to characterize the interaction among bullet, body armor, and human surrogate targets. The results exhibited three distinct loading phases during the interaction.…”
Section: Introductionmentioning
confidence: 99%